2018
DOI: 10.2471/blt.17.203265
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of mother-to-child transmission of HIV: a cross-sectional study in Malawi

Abstract: ObjectiveTo estimate the use and outcomes of the Malawian programme for the prevention of mother-to-child transmission (MTCT) of human immunodeficiency virus (HIV).MethodsIn a cross-sectional analysis of 33 744 mother–infant pairs, we estimated the weighted proportions of mothers who had received antenatal HIV testing and/or maternal antiretroviral therapy and infants who had received nevirapine prophylaxis and/or HIV testing. We calculated the ratios of MTCT at 4–26 weeks postpartum for subgroups that had mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Overall, infant outcomes were reassuring with regards to maternal‐to‐child transmission (MTCT) of HIV. MTCT occurred in only 2% of women enrolled in this cohort, comparable to MTCT among participants managed on this same regimen in other studies , and lower than the overall MTCT rate of >4% in Malawi . Most MTCT events in our cohort occurred in mother‐infant pairs where the mother had an unsuppressed viral load.…”
Section: Discussionsupporting
confidence: 58%
“…Overall, infant outcomes were reassuring with regards to maternal‐to‐child transmission (MTCT) of HIV. MTCT occurred in only 2% of women enrolled in this cohort, comparable to MTCT among participants managed on this same regimen in other studies , and lower than the overall MTCT rate of >4% in Malawi . Most MTCT events in our cohort occurred in mother‐infant pairs where the mother had an unsuppressed viral load.…”
Section: Discussionsupporting
confidence: 58%
“…This may be because all sites involved in our study had a PMTCT program. Studies have demonstrated that PMTCT programs increase HIV test rates during ante-natal care in pregnant women, promote uptake of antiretroviral drugs during pregnancy and promote HIV testing among HIV exposed infants [31][32][33][34]. We found that the percentage of contributions by age group to total children tested were closely aligned to the proportions contributed to total HIV positive found.…”
Section: Plos Onementioning
confidence: 57%
“…The National Evaluation of Malawi's PMTCT Programme (NEMAPP) study launched in 2014 to evaluate the effectiveness of Option B+ by enrolling HIV‐infected women and their infants at four to twenty‐six weeks postpartum and following them for 24 months. Within this nationally representative cohort, uptake of PMTCT services was very high: 97.8% of women knew their HIV status at enrolment and 96.3% of these were on ART . Here, we describe VL suppression rates, factors associated with VL suppression and MTCT ratios stratified by low‐detectable, undetectable and unsuppressed VL, at four to twenty‐six weeks postpartum among a sample of women enrolled in the NEMAPP study.…”
Section: Introductionmentioning
confidence: 97%